EKONOMI KELEMBAGAAN SISTEM USAHATANI PADI DI INDONESIA - BENNY RACHMAN; SUPRIYATI -; SUPENA - (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
This study was conducted in five regencies/rural which covered both java and outside java.This objective of this study are to get knowledge about the effect of policy government’sincentive and analyze Profitability Of rice farming. This results have important implicationsfor Indonesia’s food policy, namely : (1) fertilizer market seem to be working well, ascharacterized by higher market competitiveness which increased efficiency, (2) in general, atfive case districts gabah – rice market is quite well, as reflected by smaller marketing marginwith a range 4 -6 % and restively competitive, (3) the performance at rice production costshowed that in both region have cooperative and competitive advantage to produce rice, forimport substitutions. In order to improve the welfare at rice farmers the following factorshould be taken into account, i.e. Input use balanced, reducing waste during harvest and postharvest,the improvement of gabah rendement, international improvement of input – outputmarket, to enchance farmers accesibility to land, capital and technology, and diversified thesource of household income, especially from off and non – agricultural activities.